2011
DOI: 10.1530/joe-10-0458
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium intake regulates angiotensin II type 1, mineralocorticoid receptor, and associated signaling proteins in heart

Abstract: Liberal or high-sodium (HS) intake, in conjunction with an activated renin-angiotensin-aldosterone system, increases cardiovascular (CV) damage. We tested the hypothesis that sodium intake regulates the type 1 angiotensin II receptor (AT 1 R), mineralocorticoid receptor (MR), and associated signaling pathways in heart tissue from healthy rodents. HS (1 . 6% Na C ) and low-sodium (LS; 0 . 02% Na C ) rat chow was fed to male healthy Wistar rats (nZ7 animals per group). Protein levels were assessed by western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Information concerning the cardiovascular roles of striatin family members is beginning to emerge regarding their roles in rapid estrogen signaling (25) and MR activation. We have recently shown increased striatin levels in heart and aortas from mouse and rat models of MR activation, eg, with sodium restriction (7,21). In addition, we studied 2 previously described mouse models of increased ALDO levels: 1) ip ALDO administration and 2) a model of chronic ALDO-mediated cardiovascular damage after treatment with N(G)-nitro-L-arginine methyl ester plus angiotensin II.…”
Section: Discussionmentioning
confidence: 99%
“…Information concerning the cardiovascular roles of striatin family members is beginning to emerge regarding their roles in rapid estrogen signaling (25) and MR activation. We have recently shown increased striatin levels in heart and aortas from mouse and rat models of MR activation, eg, with sodium restriction (7,21). In addition, we studied 2 previously described mouse models of increased ALDO levels: 1) ip ALDO administration and 2) a model of chronic ALDO-mediated cardiovascular damage after treatment with N(G)-nitro-L-arginine methyl ester plus angiotensin II.…”
Section: Discussionmentioning
confidence: 99%
“…MR also acutely inhibits vascular Na + /K + -ATPase activity, an effect that is not altered by inhibitors of gene transcription or protein synthesis, but blocked by inhibitors of the MR and protein kinase C (PKC) (12). Increased transcription of striatin by MR indirectly counters its nongenomic stimulation of vascular smooth muscle proliferation by enhancing nongenomic ER effects (357, 376). …”
Section: Mammalian Adrenocorticosteroids and Their Receptorsmentioning
confidence: 99%
“…In vascular tissue striatin provides an anchor for the membrane association of ERα and is necessary for the vasoprotective ERα-mediated rapid nongenomic signaling through NO synthase (30, 39, 449). MR coprecipitates with both caveolin 1 and striatin (357), suggesting an interaction between the two membrane receptors and the possibility that rapid nongenomic MR effects leading to adaptive repair and hypertrophy that in excess cause deleterious vascular smooth muscle proliferation is countered by nongenomic ER effects inhibiting vascular smooth muscle proliferation, an effect enhanced by transcriptional MR effects increasing the expression of striatin (357, 376). In vitro and in vivo increases in aldosterone, including physiological increases by feeding a low sodium diet, were reported to increase striatin expression in the heart, vessels and cultured endothelial cells, thereby enhance rapid nongenomic ER effects (357,376).…”
Section: Mammalian Adrenocorticosteroids and Their Receptorsmentioning
confidence: 99%
“…The unexpected pattern of high RAAS associated with HS loading characterized a group of patients, 10% of the entire study population constituted mostly by females, with increased arterial stiffness. Data from Ricchiuti et al 24 demonstrated that an HS diet plus RAAS activation were necessary for the development of cardiovascular damage in healthy rodents, while those animals on an LS diet showed no cardiovascular impairment in spite of a greater increase in their PRA and aldosterone levels. Hollenberg showed that rapid vascular damage requires both high mineralocorticoid levels and HS intake in high-BP diabetic patients.…”
Section: Discussionmentioning
confidence: 99%